Business Rescue and Insolvency Regulation and Practice In Nigeria: The Imperatives of Globalization - Omoregie, Osaretin Kayode (Archives of Business Research, 2019)
Abstract Business rescue and insolvency regulation and practice is critical to economic development. This is especially true in the light of the unintended consequences of globalisation that may result in economics shocks and business failures. This paper argues that countries with robust business rescue and insolvency laws and practices are better able to manage the adverse impact of local and global economic shocks, attract more foreign investments and achieve faster and even development. Nigeria can benefit from reforms in business rescue and insolvency by benchmarking the reform and practice initiatives of the more advanced countries within and outside Africa. This paper makes some recommendations in this regard.